Austronesian’s Traces in Sasak: Historical Linguistics Study - Burhanuddin, Burhanuddin; Melani, Boniesta Zulandha; Saharudin, Saharudin (Jurnal Arbitrer, 2025)
The Sasak language spoken by the Sasak ethnic group in Lombok, Indonesia is one of the many Austronesian languages. As a descendant of Proto-Austronesian (PAN), Sasak is assumed to retain traces of its Austronesian heritage. This research explains the phonological characteristics of PAN in Sasak language by using the working principle in historical linguistic studies. Etymon data from Proto-Austronesian were gathered through literature review, while 200 basic vocabulary and 500 culturally vocabulary were collected through interviews. The interviews involved native speakers of four distinct Sasak dialects, with each dialect represented by three carefully selected informants based on predefined linguistic criteria. Employing a comparative method with a top-down approach, the study identified 343 PAN etyma in Sasak, of which 190 (55.39%) were determined to be inherited lexicons. Among these inherited items, 25 retained their original forms, while the remaining underwent phonological innovations. The other 153 etyma (44.61%) showed no evidence of direct inheritance. Retained Austronesian phonemes include *p, *t, *d, *m, *n, *ɲ, *s, *l, and *r —9 out of the 28 PAN phonemes—where most were regularly retained except for *r and *ɲ, which showed irregularities. Innovations were observed in *C, *c, *z, *j, *N, *S, *h, *R, *ay, *aw, and *uy. Additionally, certain phonemes, such as *k, *?, *w, *g, *ŋ, *y, *i, *u, *Ə, and *a, exhibited both retention and innovation. The retention and innovation in Sasak followed four distinct types: (1) regular retention and regular innovation; (2) regular retention and irregular innovation; (3) irregular retention and regular innovation; (4) irregular retention and irregular innovation. The high degree of innovation and non-inherited lexicon indicate that Sasak has been separated from its Austronesian ancestors for a long time. This study plays a crucial role in classifying languages within Indonesia, identifying the center of Sasak ethnic distribution on Lombok Island, and exploring the etymology of the Sasak language.